Uso do método AHP na tomada de decisão para seleção de uma rota tecnológica aplicada ao gerenciamento de resíduos sólidos urbanos no município de Caxias do Sul/RS - Conceição, Rochele Santos da (My University, 2018)
The solid waste management in Brazil, one of the axes of the basic sanitation, does not receive the necessary attention and investments to help ensure that this is no longer only a problem, but that they can bring benefits to society. The most common solutions used in Brazil are the disposal practices in the soil while other alternatives for the management of the solid waste remain underused. In this context, this study proposes the evaluation of technological routes for the management of urban solid waste in the city of Caxias do Sul, using the Analytic Hierarchy Process (AHP) decision support model to hierarchy of alternatives and selection of the most appropriate for the most sustainable management of waste. Four configurations of technological routes were proposed and were presented to invited experts, people who work directly in solid waste area, and then by pair-wise comparison evaluated the purposes linked to the environmental, social and economic criteria and to sub criteria related to them. The values that were repeated more often in each of the comparisons were inserted in the Expert Choice software. The software provided a hierarchy of the proposed alternatives. The technology route selected as the best option for the municipal waste management in Caxias do Sul was the one that integrates the technologies of recycling, composting, incineration and final disposal in landfill. Evaluating the results by criterion, it was concluded that this purpose was considered preferable in relation to the environmental and social dimensions, but referring to the economic criterion, it occupied only the third place in the order of preference. Considering that this proposal suggests the implementation of different technologies, the financial investments required are greater, but they can be minimized by the sale of materials, composite and even energy generated by the burning process. A sensitivity analysis was performed, in order to verify the reliability of the data used to apply the method, and then it can be concluded that the results would only change if there were significant changes in the weights attributed to the criteria, in which the economic represents more than 50% of the preference. The multi-criteria methodology proved to be a capable tool of assisting in the decision-making process, allowing the consideration of several evaluation factors and the integration of different guest?s opinion, and it is possible to be used by public managers for the most diverse situations of analysis and conflicts. The model is easy to understand and effective for comparing different alternatives or facing a problem of multiple choices, such as the selection of a technological route for solid waste, in which it was possible to evaluate the gains that could be achieved in relation to each proposal. It is possible to apply the method used in this study for other regions in order to propose alternative options to the current solid waste management scenarios.(sic)
Mesmo sendo um dos eixos do saneamento básico, o manejo dos resíduos sólidos não recebe a atenção e os investimentos necessários para que os resíduos deixem de se tornar apenas um problema, mas que tragam de alguma forma benefícios para a sociedade. No Brasil as soluções comumente utilizadas são as práticas de disposição no solo, sendo outras alternativas para o gerenciamento dos resíduos sólidos pouco exploradas. Neste contexto, este estudo propõe a avaliação de rotas tecnológicas para o gerenciamento dos resíduos sólidos urbanos do município de Caxias do Sul, utilizando o modelo de apoio á decisão Analytic Hierarchy Process (AHP) para hierarquização das alternativas e seleção da mais adequada para o manejo mais sustentável dos resíduos. Foram propostas quatro configurações de rotas tecnológicas, sendo estas apresentadas a especialistas convidados, atuantes na área de resíduos, que por meio da comparação por pares as avaliaram em relação aos critérios ambiental, social e econômico, e a subcritérios ligados a estes. Os valores que por mais vezes se repetiram em cada uma das comparações foram inseridas no software Expert Choice, que forneceu uma hierarquização das alternativas propostas. A classificada como melhor opção para o gerenciamento dos resíduos municipais de Caxias do Sul, foi a que se propôs a integração de tecnologias de reciclagem, compostagem, incineração e disposição final em aterro sanitário. Avaliando os resultados por critério, pode-se concluir que esta foi considerada como preferível em relação as dimensões ambiental e social, já referente ao critério econômico, esta ocupou o terceiro lugar. Tendo em vista que esta proposta sugere a implementação de diferentes tecnologias, os investimentos financeiros requeridos são maiores, mas podem ser minimizados com a venda de materiais, composto e mesmo de energia gerada pelo processo de queima. A fim de verificar a confiabilidade dos dados utilizados para aplicação do método foi realizada uma analise de sensibilidade, na qual pode-se concluir que os resultados somente sofreriam alterações se o econômico representa-se mais de 50% da preferência em relação aos demais. A metodologia multicritério mostrou-se como uma ferramenta capaz de auxiliar no processo decisório, permitindo a consideração de diversos fatores de avaliação e a integração de diferentes opiniões, podendo ser utilizada pelos gestores públicos para as mais diversas situações de analises e conflitos. O modelo é de fácil compreensão e eficaz para comparação entre diferentes alternativas ou frente a um problema de múltiplas escolhas, como na seleção de uma rota tecnológica para os resíduos sólidos, em que foi possível avaliar os ganhos que poderiam ser alcançados em relação da cada proposta. O método aplicado neste estudo pode ser replicado a outras regiões, a fim de propor opções alternativas aos atuais cenários de gerenciamento de resíduos.(sic)
Keywords: Resíduos sólidos - Caxias do Sul; Saneamento